Empower: new concept for leadership educational administrator - González Salazar, Luis Enrique (2011)
This article is an analysis of the twoguidelines sent by Dr. Claudio Gutierrez whenwas Minister of Education, in which "was empowered" tothe regional education and put into practice the principle of subsidiarity, to establish anew way of relating the regionalwith the headquarters of the Ministry and these with educational institutions. It emphasizes the potential of thisleadership concept in order to analyze the statecurrent process of "empowerment" in the AddressRegional Alajuela, viewed this as a continuum betweenautonomy and control leadership styles practiced by the five directors of the circuit 01